Yukagir Dilindeki Türkçe ve Tunguzca Alıntılara İlaveler VI - Piispaanen, Peter (Journal of Old Turkic Studies, 2021)
In this sixth part of this paper series, additional Turkic (i.e. Yakut) and Tungusic (i.e. Ewen or Ewenki) lexical borrowings into the Yukaghir languages and dialects are presented and evaluated in semantic, phonological and other considerations and viewpoints, thus providing loanword etymologies. In summary, a total of fourteen Yakut borrowings, four Tungusic and three Russian borrowings are given. An extra section of interest deals in the etymologizing of up until now quite mysteriously named Yukaghir child and youth games, and lastly some etymological notes and documentation corrections are again given. In this sixth part of this paper series, additional Turkic (i.e. Yakut) and Tungusic (i.e. Ewen or Ewenki) lexical borrowings into the Yukaghir languages and dialects are presented and evaluated in semantic, phonological and other considerations and viewpoints, thus providing loanword etymologies. In summary, a total of fourteen Yakut borrowings, four Tungusic and three Russian borrowings are given. An extra section of interest deals in the etymologizing of up until now quite mysteriously named Yukaghir child and youth games, and lastly some etymological notes and documentation corrections are again given.